Functions and evolution of FAM111 serine proteases - Welter, Allison L.; Machida, Yuichi J. (Frontiers in Molecular Biosciences, 2022)
Proteolysis plays fundamental and regulatory roles in diverse cellular processes. The serine protease FAM111A (FAM111 trypsin-like peptidase A) emerged recently as a protease involved in two seemingly distinct processes: DNA replication and antiviral defense. FAM111A localizes to nascent DNA and plays a role at the DNA replication fork. At the fork, FAM111A is hypothesized to promote DNA replication at DNA-protein crosslinks (DPCs) and protein obstacles. On the other hand, FAM111A has also been identified as a host restriction factor for mutants of SV40 and orthopoxviruses. FAM111A also has a paralog, FAM111B, a serine protease with unknown cellular functions. Furthermore, heterozygous missense mutations in FAM111A and FAM111B cause distinct genetic disorders. In this review, we discuss possible models that could explain how FAM111A can function as a protease in both DNA replication and antiviral defense. We also review the consequences of FAM111A and FAM111B mutations and explore possible mechanisms underlying the diseases. Additionally, we propose a possible explanation for what drove the evolution of FAM111 proteins and discuss why some species have two FAM111 proteases. Altogether, studies of FAM111 proteases in DNA repair, antiviral defense, and genetic diseases will help us elucidate their functions and the regulatory mechanisms.